Comparative Analysis of Lutein Content in Leaves and Fruit of Lycium barbarum: Implications for Medicinal Applications: Analisis Perbandingan Kandungan Lutein pada Daun dan Buah Lycium barbarum: Implikasi untuk Aplikasi Obat - Omaima Saddam Zirjawi; Ula M Noor Almousawi; Amjed Haseeb Khamees (Academia Open, 2024)
Herbal medicine stands as a pivotal realm of contemporary research, offering substantial benefits with minimal side effects. Lycium barbarum, recognized for its abundant bioactive compounds, holds promise in treating various ailments, particularly in antiaging and antioxidative capacities. Carotenoids, notably lutein and zeaxanthin, constitute key bioactive compounds with diverse functions in both plant physiology and human health, including photo protection against intense light and detoxification of reactive oxygen species. This study meticulously examines the lutein content within leaves and fruit of L. barbarum, employing a uniform extraction method and solvent. The investigation illuminates significant variations in lutein content between the leaves and fruit, shedding light on potential applications in herbal medicine and nutraceuticals. Highlight: Herbal Medicine Advancements: This study underscores the pivotal role of herbal medicine in contemporary research, emphasizing its potential for providing substantial benefits with minimal side effects. Lycium barbarum's Therapeutic Potential: The research highlights Lycium barbarum's significance due to its rich array of bioactive compounds, particularly in addressing antiaging and antioxidative requirements. Bioactive Carotenoids in Focus: The study delves into the functions of essential bioactive compounds, lutein and zeaxanthin, elucidating their roles in plant physiology and human health, including their photoprotective and detoxifying properties. Keyword: Herbal Medicine, Lycium Barbarum, Bioactive Compounds, Carotenoids, Lutein Content